National public policy and its framing of startups Algeria case - FENGHOUR, Abderrezzak (The International tax journal, 2026)
Startups are considered an alternative strategy in the economic field in Algeria, as we no longer wish to rely on the hydrocarbons sector, as stated by the President of the Republic. However, it is time to utilize frameworks, competencies, and invest in human resources and their intellectual capital in various fields. All of this falls under the umbrella of national public policy and its framing of startups for their success, to rely on them to raise the level of the economy, reduce unemployment, improve the standard of living, and even encourage competencies to engage in independent work according to the dictates of laws regarding work and how to establish medium or small-sized enterprises. Consequently, this study aims to answer the following question: How does national public policy contribute to framing startups in Algeria?